Herbal prevention and treatment of nipple trauma and/or pain in Iranian studies: a systematic review - Nayereh As'adi; Nourossadat Kariman (Shahrekord University of Medical Sciences, 2018)
Introduction: Adequate nutrition during infancy is essential for lifelong health and wellbeing. However, painful nipple trauma is problematic for mothers and may lower the prevalence of breastfeeding. This systematic review was conducted to assess herbal prevention and treatment of nipple trauma and/or pain in Iranian studies. Methods: All the Iranian indexed publications in English and in Persian were searched with the key words of "nipple trauma" and "nipple pain" from inception to 26 December 2017 on indexing sites of PubMed, Proquest, Scopus, Science Direct, Medline, SID, IranMedex, Magiran, and Google Scholar. The results were reported qualitatively. Eleven randomized clinical trials (RCTs) with total sample size of 1218 were included in this systematic review. Different herbal remedies were used in included articles. The articles were investigated through Jadad scale. Studies that scored 3 or more on Jadad scale were selected. The results were reported qualitatively. Only RCTs were considered. Results: Pistacia atlantica (Saqez), Ziziphus jujuba, curcumin, menthol, Aloe vera, Calendit - E (Calendula officinalis and Echinacea angustifolia) were the most effective treatments of nipple trauma and/or pain. In one study, peppermint water was more effective than breast milk in preventing nipple cracks and in another study nipple crack was less in women using peppermint compared with those who used lanolin ointment or placebo. Conclusion: As each study used a special medicinal plant in this review, judgement about the definitive efficacy of these remedies needs further precise studies.